Evaluation of the Outcome of Antiviral Therapy among Individ-uals Infected HIV-1 in Suqian District of Jiangsu Province, China - Zhenjiang Zhang; Jing Su; Xin Shen; Bing Pei; Fang Zhu; Huichun Ji; Tingting Shi; Youde Yan (Tehran University of Medical Sciences, 2021)
Background: To evaluate the condition of antiviral therapy (ART) for individuals infected HIV-1 in Suqian district of Jiangsu Province, China. Methods: Altogether, 561 HIV-positive patients who received antiviral therapy in Suqian district in 2019 were recruited. EDTA anticoagulated blood was collected and separated to obtain the plasma samples. Viral load (VL) were tested for evaluating the outcome of ART. Then samples with VL beyond 1000IU/mL were used to conduct the molecular test in order to master the characters of HIV-1 and the prevalence of resistance strains. Results: VL results showed that the virus in 91.1% of the patients who received continuous antiviral treatment for more than 6 months were effectively inhibited (VL ≤ 1000 IU / ml). Among the 50 patients who failed in the treatment, 46 HIV-1 pol gene sequences were obtained, and the positive rate was 92.0%. The most prevalent strain was CRF_ 07bc (32.6%), and new epidemic strains, such as 67_01B、79_0107、87_cpx, were popular in this district. Drug resistance test results showed that 56.5% of the patients failed in antiviral treatment due to drug resistance, mainly resistant to the national first-line antiviral drug 3TC. Drug-resistant strains were not found in 43.5% of the patients. Conclusion: ART achieved a satisfied result in Suqian district, but the main cause resulting in ART-failure was resistant, so it is very necessary to enhance the education of adherence prior to the initiation of ART.